2005
DOI: 10.1074/jbc.m412017200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor (VEGF)-A165-induced Prostacyclin Synthesis Requires the Activation of VEGF Receptor-1 and -2 Heterodimer

Abstract: We previously reported that vascular endothelial growth factor (VEGF)-A 165 inflammatory effect is mediated by acute platelet-activating factor synthesis from endothelial cells upon the activation of VEGF receptor-2 (VEGFR-2) and its coreceptor, neuropilin-1 (NRP-1). In addition, VEGF-A 165 promotes the release of other endothelial mediators including nitric oxide and prostacyclin (PGI 2 ). However, it is unknown whether VEGF-A 165 is mediating PGI 2 synthesis through VEGF receptor-1 (VEGFR-1) and/or VEGF rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 54 publications
(84 reference statements)
4
83
0
1
Order By: Relevance
“…[7][8][9][10][11] Hypoxia and endothelial shear stress in HT are known to be major stimuli for sFLT-1 expression and release. [12][13][14][15][16] Furthermore, sFLT-1 is stimulated by the vascular sympathetic nervous system and has been reported to be elevated in patients with HT.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Hypoxia and endothelial shear stress in HT are known to be major stimuli for sFLT-1 expression and release. [12][13][14][15][16] Furthermore, sFLT-1 is stimulated by the vascular sympathetic nervous system and has been reported to be elevated in patients with HT.…”
mentioning
confidence: 99%
“…In another in vitro model, the VEGF-dependent differentiation of a subset of human bone marrow-derived cells into vascular precursors, and subsequent proliferation of these cells, required the activation of a VEGFR-2/NRP-1-dependent signaling pathway (Fons et al, 2004). Finally, VEGF promotion of the synthesis and release of prostacyclin (PGI 2 ), an important mediator of angiogenesis, is thought to be mediated via NRP-1 binding (Neagoe et al, 2005). The angiogenic effects regulated through VEGF binding to NRP-2 are less well characterized and appear to be modulated differently from the effects controlled by NRP-1.…”
Section: Vegf Receptorsmentioning
confidence: 99%
“…Pre-assembled heterodimer receptors of VEGFR-2 and VEGFR-3 subunits have been isolated from primary lymphatic endothelial cells 28,29 and detected in situ on angiogenic sprouts 30 . Heterodimerization between VEGFR-1 and VEGFR-2 subunits (VEGFR 1 − 2 ) has been detected in cell-free systems 13 and in endothelial cell lines 19,[31][32][33] . A computational model of VEGF receptor subunit dimerization concluded that a tenfold excess of one VEGF receptor subunit would result in minimal homodimerization of the less abundant receptor 34 .…”
mentioning
confidence: 99%
“…Therefore, dissection of VEGFR 1 − 2 heterodimerspecific function has been challenging. Receptor subunit knockdown and use of cell lines expressing specific receptors indicate that prostacyclin release 33 and biphasic calcium induction 32 is likely to be the result of VEGFR 1 − 2 activation.…”
mentioning
confidence: 99%